Growth Response, Nutrient Digestibility and Organ Characteristics of Broiler Chicken Fed Graded Levels of Kola Pod Husk Meal (KPHM) in a Derived Savannah Zone of Nigeria - Emiola, I.A.; Ojebiyi, O.O.; Hamzat, R.A.; Rafiu, T.A.; Ogunwuyi, G.; Lawal, A. (International Journal of Poultry Science, 2006)
One hundred and forty-four (144) day old Anak 2000 broiler chicks were used to investigate the growth response as well as organ characteristics of broiler chickens fed graded levels of kola pod husk meal (KPHM). The birds were randomly allotted to four dietary treatments groups containing 0%, 10%, 20% and 30% KPHM. There were two replicates per treatments with 18 birds per replicate in a completely randomized design. The birds placed on control diet utilized their feed more efficiently (P< 0.05) than other treatments. The broilers fed 10% and 20% KPHM were able to convert the diet more efficiently (P< 0.05) than the broilers on 30% KPHM. Treatment effects on weight gain, feed: gain ratio, dressed weight, length of small intestine, length of colon, length of caecum, weights of kidney and lung were significantly (P< 0.05) different. Growth rate decreased significantly (P< 0.05) with increasing level of KPHM in the diet. However, no significant (P>0.05) difference was observed in protein efficiency ratio, nitrogen retention, dry matter digestibility and crude fibre digestibility of the birds fed different diets. It could be concluded that KPHM inclusion in broiler diet up to 10% dietary level will adversely affect the performance of broilers.